Sotos syndrome with marked overgrowth in three Japanese patients with heterozygous likely pathogenic NSD1 variants: case reports with review of literature - Yohei Masunaga; Hiroyuki Ono; Yasuko Fujisawa; Kiyosu Taniguchi; Hirotomo Saitsu; Tsutomu Ogata (Endocrine Journal)
We report three Japanese patients with Sotos syndrome accompanied by marked overgrowth, i.e., a 2 8/12-year-old boy with a height of 105.2 cm (+4.4 SD) (patient 1), the mother of patient 1 with a height of 180.8 cm (+4.1 SD) (patient 2), and a 12 10/12-year-old girl with a height of 189.4 cm (+6.3 SD) (patient 3). In addition to the marked overgrowth (tall stature), patients 1–3 exhibited Sotos syndrome-compatible macrocephaly and characteristic features, whereas intellectual and developmental disabilities remained at a borderline level in patient 1 and were apparently absent from patients 2 and 3. Thus, whole exome sequencing was performed to confirm the diagnosis, revealing a likely pathogenic c.6356A>G:p.(Asp2119Gly) variant in NSD1 of patients 1 and 2, and a likely pathogenic c.6599dupT:p.(Ser2201Valfs*4) variant in NSD1 of patient 3 (NM_022455.5). The results, in conjunction with the previously reported data in nine patients with marked overgrowth (≥4.0 SD), imply that several patients with Sotos syndrome have extreme tall stature even in adulthood. Thus, it is recommended to examine NSD1 in patients with marked overgrowth as the salient feature.